PEMANFAATAN BAKTERI KITINOLITIK DALAM MENGHAMBAT PERTUMBUHAN Curvularia sp. PENYEBAB PENYAKIT BERCAK DAUN PADA TANAMAN MENTIMUN - Andini - Hanif; Dwi Suryanto; Isnaini Nurwahyuni (Saintia Biologi, 2012)
A study on about the utilization of chitinolytic bacterial isolates to inhibit growth of Curvularia sp. causal agent of leaf spot disease of cucumber was done in Laboratory of Pest and Disease, Medan Johor, UPT-Balai Protection Plant and Horticulture I and Laboratory Microbiology Departement of Biology, Faculty of Mathematics and Natural Sciences, University of Sumatera Utara, Medan. Six chitinolytic isolates were tested in vitro to inhibit growth of Curvularia sp.. The result showed that Bacillus sp. BK13 inhibited more with inhibition zone of 2,75 cm and Enterobacter sp. BK15 with inhibition zone of 2,55 cm, whereas Enterobacter sp. PB17 showed the lowest inhibition zone of 1,3 cm. Soaking seed treatment in chitinolytic bacterial suspension reduced the percentage of leaf spot. Enterobacter sp. BK15 showed more ability (50%) to inhibit leaf spot attack.   Keywords: Bacillus sp. BK13, cucumber, Curvularia sp., Enterobacter sp. BK15, leaf spot